1978
DOI: 10.1002/1520-6807(197801)15:1<111::aid-pits2310150121>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Affective and associative qualities in the learning styles of Chicanos and Anglos

Abstract: The role of affective and associative meaningfulness in the learning styles of Chicanos and Anglos was examined in the present study. Sixty‐four Chicano and Anglo undergraduates were compared on their learning of affectively and associatively assessed consonant‐vowel‐consonant trigrams. Chicanos did not differ from Anglos in their reliance on the affective relative to the associative dimension of meaningfulness in their learning style. However, Chicanos differed significantly from Anglos in affective learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Carrillo (1982), for example, noted that interpersonal relationships in Mexican culture are characterized by high levels of affection. In Mexican culture, affect is more openly accepted and more highly valued than in Anglo culture (Garza, 1978;Guerra, 1970;Ramirez & Castaneda, 1974). The sentiment is best captured by Murillo's (1976) statement that in Mexican American culture, "It is through ... an ability to experience, in response to environment, emotional feelings and to express these to one another and share them that one experiences the greatest rewards and satisfactions in life" (p. 100).…”
Section: Mexican Culture and Emotionmentioning
confidence: 99%
“…Carrillo (1982), for example, noted that interpersonal relationships in Mexican culture are characterized by high levels of affection. In Mexican culture, affect is more openly accepted and more highly valued than in Anglo culture (Garza, 1978;Guerra, 1970;Ramirez & Castaneda, 1974). The sentiment is best captured by Murillo's (1976) statement that in Mexican American culture, "It is through ... an ability to experience, in response to environment, emotional feelings and to express these to one another and share them that one experiences the greatest rewards and satisfactions in life" (p. 100).…”
Section: Mexican Culture and Emotionmentioning
confidence: 99%
“…Mexican-Americans come from a culture that typically is characterized by human reladonal concerns, personcenteredness, and the open acceptance of affective temperament (Guerra, 1970;Ramirez & Gasteneda, 1974). Indeed, striking psychodynamic and sociocultural differences between these two groups have been demonstrated in a number of recent studies (e.g., Garza, 1978;Garza & Nelson, 1973;Kagan, 1974;Kagan & Garlson, 1975;Lipton & Garza, 1978;Ramirez & Price-Williams, 1974).…”
mentioning
confidence: 99%
“…In his doctoral dissertation, he found that Chicanos differ significantly from Anglos in affective learning style, showing a greater propensity to learn materials they like and less propensity to learn materials they dislike than do whites (16). And in a study he published with Widlak in 1976, the researchers found that there are:…”
Section: Affective and Emotional Qualitiesmentioning
confidence: 88%